Transcriptomic analysis of Chlorella sp. HS2 suggests the overflow of acetyl‐CoA and NADPH cofactor induces high lipid accumulation and halotolerance. (30th December 2020) - Yun, Jin‐Ho; Pierrelée, Michaël; Cho, Dae‐Hyun; Kim, Urim; Heo, Jina; Choi, Dong‐Yun; Lee, Yong Jae; Lee, Bongsoo; Kim, HyeRan; Habermann, Bianca; Chang, Yong Keun; Kim, Hee‐Sik
Abstract: Previously, we isolated Chlorella sp. HS2 (referred hereupon as HS2) from a local tidal rock pool and demonstrated its halotolerance and high biomass productivity under different salinity conditions. To further understand acclimation responses of this alga under high salinity stress, we performed transcriptome analysis of triplicated culture samples grown in freshwater and marine conditions at both exponential and stationary growth phases. The results indicated that the transcripts involved in photosynthesis, TCA, and Calvin cycles were downregulated, whereas the upregulation of DNA repair mechanisms and an ABCB subfamily of eukaryotic type ABC transporter was observed at high salinity condition. In addition, while key enzymes associated with glycolysis pathway and triacylglycerol (TAG) synthesis were determined to be upregulated from early growth phase, salinity stress seemed to reduce the carbohydrate content of harvested biomass from 45.6 dw% to 14.7 dw% and nearly triple the total lipid content from 26.0 dw% to 62.0 dw%. These results suggest that the reallocation of storage carbon toward lipids played a significant role in conferring the viability of this alga under high salinity stress by remediating high level of cellular stress partially resulted from ROS generated in oxygen‐evolving thylakoids as observed in a direct measure of photosystem activities. Abstract : Allocation of storage carbon toward the synthesis of lipids seemed to play a critical role in conferring the halotolerance of a Chlorella isolate by remediating excess oxidative stress experienced in photosystems.